The Relationship between Pre-service Primary School Teachers’ Beliefs about Mathematics and Critical Thinking Dispositions - Mehmet Koray Serin, Gökhan Uyanık, Lütfi İncikabı, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
The aim of this study is to determine the level of relationship between pre-service primary school teachers’ mathematics-related beliefs and their critical thinking disposition. The research follows a quantitative paradigm in the data context and is designed according to the relational survey method. The participants were the third and fourth grade students who were studying at the Department of Primary School Education at the Faculty of Education in a state university in Turkey in the 2014-2015 academic year. Two main data collection tools were used in the research. One of them is the Mathematics Related Beliefs Scale (MRBS) developed by Kayan, Haser and Işıksal-Bostan (2013) and the other is the California Critical Thinking Disposition Inventory which had been adapted by Kökdemir (2003) into Turkish. In the data analysis, mean, independent samples t- test and Pearson moments correlation coefficient were used. According to the findings, it was found that the pre-service primary school teachers agreed more on constructivist belief statements than traditional beliefs. Also, critical thinking dispositions were seen to be partly positive. There was no significant difference in pre-service teachers' maths-related beliefs as well as in their critical thinking dispositions compared to the class level variables. Finally, according to the results of correlation analysis, a low level of positive correlation between the constructivist beliefs dimension and the critical thinking dispositions scale factors was found.